Research on social desirability levels of individuals with disabilities living in the province of batman in terms of the various variables - Abdullah Manap; Erdal Cetın; Erhan Sahın; Haci Sahın (Selcuk University, 2015)
Generally social desirability is defined as individuals give socially desirable answers or tend to show an attitude towards a positive impression within the framework of the relations between an individual and a group, an individual and a society, which is a basic equation of social psychology. Crowne and Marlowe tried to explain social desirability as ''to imitate a good thing'', ''to give a culturally accepted answer'' or ''to give a prejudicial reaction to an approval request''. Also, Edward defined it as a self-definition tendency which is socially desirable and undesirable between the scale values. In this context, this study focused on whether there were significant differences in the social desirability levels of individuals with disabilities living in the province of Batman in terms of various variables such as age, gender, monthly income, sport performance, sport performance frequency. In this study " the Two-Dimension Social Desirability Scale" which was developed by Akın, was applied to 70 people with disabilities living in Batman. The sample group of 70 people was considered to have different ages, marital status, monthly income and education level. The sample group was also asked whether they did sport or how often they did sport. According to the evaluation with the SPPS 17.0 statistical analysis program, the social desirability levels were higher in the males rather than females and in the married ones than single ones. Also, there was a significant difference between the social desirability levels and the sport performance frequencies in the individuals doing sport.